A critical analysis on inefficiencies in procurement process in roads and highways - Daud, A. Z. M. Farhan (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.